2019
DOI: 10.1088/1361-6463/ab01a9
|View full text |Cite
|
Sign up to set email alerts
|

Highly reliable multilevel resistive switching in a nanoparticulated In2O3 thin-film memristive device

Abstract: The present report deals with the development of a cost-effective, solution-processable and nanoparticulated In 2 O 3 thin-film memristive device for application in multilevel resistive random access memory (RRAM). The structural, morphological, elemental and electrical characterizations are carried out with the help of x-ray diffractometry, scanning electron microscopy, photoluminescence spectroscopy, Fourier transform infrared spectroscopy, x-ray photoelectron spectroscopy and a memristor characterization sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The switching speed was found to be 100 ns. This type of bipolar switching using organic molecules is very promising for applications such as memory, 38 computing, 39 sensing, 40 and logic circuits. 41 In these bipolar switching devices, the SET (transition from HRS to LRS) operation represents a "writing" operation for memory applications.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The switching speed was found to be 100 ns. This type of bipolar switching using organic molecules is very promising for applications such as memory, 38 computing, 39 sensing, 40 and logic circuits. 41 In these bipolar switching devices, the SET (transition from HRS to LRS) operation represents a "writing" operation for memory applications.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The switching speed was found to be 100 ns. This type of bipolar switching using organic molecules is very promising for applications such as memory, computing, sensing, and logic circuits …”
Section: Results and Discussionmentioning
confidence: 99%
“…The RS phenomenon has been observed in several materials, including chalcogenides [19], selenides [20], graphene oxide [21], organic polymer composites [22] and transition metal oxides [2,23,24]. Among all these materials, transition metal oxide based RS devices have been studied extensively in the past few years [6,[25][26][27][28]. Several types of mechanisms such as (i) thermochemical memory devices [29], (ii) electrochemical metallization memory (ECM) [30,31], and (iii) valence change memory [31] have been proposed to explain RS in these materials.…”
Section: Introductionmentioning
confidence: 99%
“…A native oxide layer on electrode material could intensify the performance of RRAM with respect to environmental stability, reliability, and R ON /R OFF ratio. Frank et al showed that the thin oxide layer of Al 2 O 3 improved the device’s switching mechanism and reliability [ 22 ]. Zinc oxide (ZnO) has proven its potential capability in RRAM performance due to its large band gap (3.37 eV) and high exciton binding energy (B.E) (60 MeV) at absolute temperature.…”
Section: Introductionmentioning
confidence: 99%